Proving public interest : the growing impact of evidence in free movement case law - Shuibhne, nic Niamh (2013)
Explores the standard that States must satisfy to prove their public interest claims successfully. Argues that a critical information gap on what the Court of Justice expects defendant States to establish has been narrowed through a more concerted focus on proof in recent case law; but that significant issues still demand further attention.